Analisis kesulitan kemampuan pemecahan masalah matematis siswa SMP materi persamaan garis lurus berdasarkan teori newman - Phani Yuliyani; Ratna Sariningsih; Euis Eti Rohaeti (IKIP Siliwangi, 2023)
The purpose of this study was to find out the difficulties faced by students in the ability to solve mathematical problems of Straight Line Equation material. This type of research is descriptive qualitative, and data collection is carried out as instrumental questions with 4 questions. The subjects of the study were class VIII students numbering 10 people. The results of the researcher's analysis showed that students’ mathematical problem solving abilities in straight line equation material were still low. Students difficulties in reading problems in this straight line equation material, students having difficulty reading graphs on the questions presented, students' lack of understanding of constructing known and asked data used to solve problems, difficulties in determining formulas that are appropriate to the questions presented, lack of accuracy and ignorance of the prerequisite material related to the problem, and answering questions at random, so that students cannot solve them correctly. This difficulty is caused by students' lack of accuracy when reading questions in the form of descriptions, not paying attention to the teacher when explaining and not understanding graphical questions and the way students think about mathematical problems is difficult.